Historická a teoretická východiska psychomotorické terapie - Hátlová, Běla; Adámková Ségard, Milena; Wedlichová, Iva; Louková, Tereza; Bašný, Zdeněk (Československá psychologie, 2014)
The basic therapeutic mean of modern psychiatry is pharmacotherapy. It, however, does not provide the patients the sufficient opportunity to act for their recovery and puts them in a position of passive recipients of treatment. One of the supporting policies which affect the negative symptomatology is the physical activity that encourages inherently the patient to active participation in therapy and can even strengthen his/her resistance to the daily stress. The psychomotor therapy is elaborated on this basis since the 19th century. It is considered an alternative therapy and can become the component of some psychotherapeutic approaches, e.g. behavioral, cognitive, cognitive-behavioral, and psychodynamic therapy. It includes the medical, psychological, agogic, kinesiologic, and physiotherapeutic components. The aim of the study is to highlight the resources of the present psychomotor therapy.
Keywords: Psychotherapy; Mental Disorders; duševní poruchy; kombinovaná terapie; Exercise Therapy; Public Assistance; Humans; Combined Modality Therapy; podpora z veřejných prostředků; lidé; psychoterapie; terapie cvičením